Compartmentalization of Hepatitis C Virus (HCV) during HCV/HIV Coinfection - Blackard, Jason T. (2007)
Extrahepatic replication has important implications for the transmission and treatment of hepatitis C virus (HCV). We analyzed longitudinal HCV diversity in peripheral-blood mononuclear cells (PBMCs) and serum during HCV monoinfection and HCV/HIV coinfection to determine whether distinct amino acid signatures characterized HCV replicating within PBMCs. Analysis of E1-HVR1 sequences demonstrated higher serum genetic distances among HCV/human immunodeficiency virus (HIV)–coinfected persons. Moreover, consensus PBMC sequences were rarely identical to those in the corresponding serum, suggesting divergence in these 2 compartments. Three of 5 HCV/HIV-coinfected participants showed evidence of HCV compartmentalization in PBMCs. Additionally, signature sequence analysis identified PBMC-specific amino acids in all HCV/HIV-coinfected persons. To our knowledge, this is the first study to identify specific amino acids that may distinguish HCV variants replicating in PBMCs. It is provocative to speculate that extrahepatic HCV diversity may be an important determinant of treatment response and thus warrants additional study, particularly during HCV/HIV coinfection.